Numerical Treatment of First Order Volterra Integro-Differential Equation Using Non-Polynomial Spline Functions - Esa, Rawaa I.; Saleh, Atefa J. (Iraqi Journal of Science, 2020)
The approach given in this paper leads to numerical methods to find the approximate solution of volterra integro –diff. equ.1st kind. First, we reduce it from integro VIDEs to integral VIEs of the 2nd kind by using the reducing theory, then we use two types of Non-polynomial spline function (linear, and quadratic). Finally, programs for each method are written in MATLAB language and a comparison between these two types of Non-polynomial spline function is made depending on the least square errors and running time. Some test examples and the exact solution are also given.